Moral earthquakes and our response: Can ethics make a difference? - Richardson, RN (Stellenbosch Theological Journal, 2016)
The major conflicts that shake our world are often driven by deep seated religious and cultural differences – they seem so overwhelming and run so deep that a seismological metaphor seems appropriate. How can ethics help to resolve these conflicts when much twentieth century ethical theory understood its role to be “neutral as regards actual conduct”? Alasdair MacIntyre rightly criticised the ethics of the Enlightenment project, but his own positive proposals do not seem to offer a clear way to address major moral conflicts. Can Christian ethics and the Christian church play a constructive role in our multi-faith and multicultural world? A practical ecumenical proposal is considered and is seen to offer a bridge across the theory-action divide; to draw together some positive suggestions of MacIntyre and other socio-ethicists; and to foreground the important role that the church might play in responding to major moral conflicts.